Nitrogen dynamics and yield performance of an elite bread wheat line with BNI capacity expressed in an alkaline soil - Karwat, Hannes; Kishii, Masahiro; Cárdenas-Castañeda, María Elena; Ibba, Maria Itria; Kommerell, Victor; Bentley, Alison R.; Braun, Hans-Joachim; Ortiz-Monasterio, Iván (Elsevier, 2025)
Wheat with biological nitrification inhibition (BNI) has demonstrated effectiveness in acidic soils. However, BNI expression under alkaline soil conditions have not been documented in field studies. Here, we present the first field-based evidence of BNI effects in alkaline soils (pH 8.6-8.7), using an elite spring wheat line (ROELFS) carrying the Lr#N short arm (+BNI) introgressed from Leymus racemosus which confers BNI activity as compared to ROELFS without the translocation arm (-BNI). BNI expression was evidenced by lower soil nitrate in three irrigated wheat trials conducted in northwestern Mexico. In one trial (Exp 1), soil nitrate levels of the translocation line (+BNI) were 24-37 % lower than in the control line (-BNI) after the second application of ammonium-N fertilizer. Reductions were observed both in the row and in the furrow. In another trial (Exp 3), the most pronounced nitrate difference occurred approximately one month after the second ammonium-N application, with nitrate levels in +BNI plots reduced by 73-77 %. The translocation line also exhibited higher flag leaf nitrate concentrations, likely associated with the decreased soil nitrate concentrations. In vitro potential nitrification rates, measured one week after ammonium-N application, were 27-32 % lower in soil associated with the +BNI line compared to the control, across two consecutive years. Phenologically, the +BNI line reached anthesis and flowering later than the control, regardless of additional N fertilization. In two experiments, grain yield did not differ significantly between +BNI and control, while in one trial it was reduced, due to fewer grains per spike and a lower spike density. The harvest index was consistently lower in +BNI than -BNI under high N input. Nevertheless, grain protein and grain N uptake and grain weight were not statistically different between the lines. We conclude that BNI can significantly reduce nitrification with a spatially and temporally impact under alkaline, high N conditions. This represents a potentially important environmental benefit for a wide range of wheat systems globally. Further research is needed to evaluate the effects of the Lr#N short arm on yield and quality in other elite lines. Additionally, potential negative effects on gluten quality from the wild donor genome should be considered in future breeding efforts.